1994
DOI: 10.1055/s-0038-1642499
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel – a Platelet Inhibitor which Inhibits Thrombogenesis in Non-Anticoagulated Human Blood Independently of the Blood Flow Conditions

Abstract: SummaryThe goal of the present study was to investigate the effect of 7 and 14 days of daily oral administration of 75 mg clopidogrel on collagen-induced thrombogenesis in flowing non-anticoagulated human blood. Blood was drawn directly from an antecubital vein over immobilised collagen type III fibrils positioned in a parallel-plate perfusion chamber. The wall shear rates at the collagen surface were those characteristic for veins (100 s−1), and for medium sized (650 s−1) and moderately stenosed (2600 s−1) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…This physical effect was apparently enhancing the platelet-collagen adhesion at 2600 s" 1 and probably also at 650 s~\ even though aspirin had only marginal effect on the thrombus volume. Similar findings were previously observed in studies with the platelet inhibitors clopidogrel 16 and the reversible TxA 2 receptor antagonist HN-11500 17 in the same experimental model and at similar experimental conditions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This physical effect was apparently enhancing the platelet-collagen adhesion at 2600 s" 1 and probably also at 650 s~\ even though aspirin had only marginal effect on the thrombus volume. Similar findings were previously observed in studies with the platelet inhibitors clopidogrel 16 and the reversible TxA 2 receptor antagonist HN-11500 17 in the same experimental model and at similar experimental conditions.…”
Section: Discussionsupporting
confidence: 78%
“…16 Increased urinary excretion of the stable thromboxane metabolite 2,3-dinorthromboxane R2 has been observed in smokers of both sexes, 7 suggesting that cigarette smoking may increase platelet reactivity and vasoconstnction through augmented TxA 2 formation. 28 The present study was carried out to investigate whether cigarette smoking affected collagen-induced thrombogenesis in flowing nonanticoagulated human blood and to quantify the effect of aspirin-blocked TxA 2 synthesis on thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Prothrombin fragment F1ϩ2 plasma levels were similar throughout the study and between the groups. This is consistent with other published data 24,25 showing that thrombin generation is not directly reduced with thienopyridines.…”
Section: Acute Antithrombotic Effect Of a Front-loaded Regimen Of Closupporting
confidence: 83%
“…31 To the best of our knowledge, only 1 study focused on the inhibition of thrombogenesis by clopidogrel in humans. 24 In this study, a standard regimen of clopidogrel significantly inhibited thrombus formation in healthy male subjects after 2 weeks of a standard regimen of clopidogrel. We found that the inhibition was significant at day 8 in patients with atherosclerosis receiving chronic aspirin therapy when a standard regimen of clopidogrel was used.…”
Section: Antithrombotic Effect Of Clopidogrel Administration In Athermentioning
confidence: 99%